Les foyers d’en-haut.La montagne, emblème du paradoxe de l’intégration des requérant·es d’asile en Suisse - Viviane Cretton (Revue de Géographie Alpine)
This article analyses “what the mountain does” to people seeking asylum in Switzerland. It focuses on their experiences while they are accommodated in collective reception centres at high altitudes. At the level of Swiss society, asylum seekers are subject to an “integration” injunction, despite the uncertain outcome of their application. When the waiting and uncertainty imposed by the asylum procedure is experienced at an altitude of more than 1300 metres, the feeling of being kept away from life in urban centres is reinforced and the emotional burden exacerbated.The specific experiences of collective accommodation in the mountains, experienced by asylum seekers – and by the professionals or volunteers accompanying them – are expressed in their story telling of the place. Far from the tourist and romantic representations of the mountains, the oppositions between the top and the bottom (the valley and the plain), between the periphery and the centre (the mountain and the town) run repeatedly through the collected narratives. They maintain a representation of the mountain as a non-place of social life, an isolated place, as opposed to cities on the plain. When the reception "above" lasts, it sustains a process of social effacement "below" which makes the injunction to integrate into Swiss society eminently paradoxical.